Effect of burial history on diagenetic and reservoir-forming process of the Oligocene sandstone in Xihu sag, East China Sea Basin. (February 2020) - Wang, Wenguang; Lin, Chengyan; Zhang, Xianguo; Dong, Chunmei; Ren, Lihua; Lin, Jianli
Abstract: Porosity evolution history, hydrocarbon charging periods, diagenetic and reservoir-forming characteristics of low-permeability and tight sandstone are presented in this study. The interpretation is based on information including thin section, scanning electron microscope, homogenization temperature of fluid inclusion, bulk rock X-ray diffraction analysis, clay X-ray diffraction analysis and stable isotopic composition. These sandstones are located in the Oligocene E3 h Formation in the Xihu sag, East China Sea Basin, East China. Five diagenetic events in the H3, H4 and H5 members were determined, including connate alkaline pore water of the Oligocene sandstone, meteoric water leaching in late Miocene, organic acids and CO2 acidic fluids in early-middle Miocene, reservoir temperature decrease induced by tectonic uplift, and alkaline diagenetic environment from late Miocene to present day. Porosity evolution history of different grain-size lithology were evaluated by basin modelling and test data. The medium sandstone and coarse sandstone of the H3 member and medium sandstone of the H4 member not reached the tight state in the geologic time. The fine sandstone of the H4 member entered the tight state at 12 Ma, suffered acidic fluids to improve the tight state in late stage, and entered the tight state again since 6.5 Ma. The medium sandstone, fine sandstone and siltstone in the H5 member entered the tight state at 13.5Ma, 16Ma and 19Ma, respectively. Three hydrocarbon charging periods were determined, including 15.5 Ma-10.4 Ma in the middle Miocene, 9.6 Ma-7.0 Ma in the late Miocene and 6.2 Ma-0.0 Ma from the late Miocene to present day. Three diagenetic and reservoir-forming patterns were proposed, including accumulation without tightness, accumulation after tightness-improving reservoir quality with acidic fluid-accumulation while tightness, accumulation after tightness. The burial history cannot be ignored in the diagenetic events, porosity evolution history and hydrocarbon charging periods of similar low-permeability and tight sandstone in sedimentary basins. Highlights: Five diagenetic events were investigated. Porosity evolution history were evaluated. Three diagenetic and reservoir-forming patterns were proposed.